Cathepsin B is up-regulated and mediates extracellular matrix degradation in trabecular meshwork cells following phagocytic challenge. - Kristine Porter; Yizhi Lin; Paloma B Liton (PLoS ONE)
Cells in the trabecular meshwork (TM), a tissue responsible for draining aqueous humor out of the eye, are known to be highly phagocytic. Phagocytic activity in TM cells is thought to play an important role in outflow pathway physiology. However, the molecular mechanisms triggered by phagocytosis in TM cells are unknown. Here we investigated the effects of chronic phagocytic stress on lysosomal function using different phagocytic ligands (E. coli, carboxylated beads, collagen I-coated beads, and pigment). Lysotracker red co-localization and electron micrographs showed the maturation of E. coli- and collagen I-coated beads-containing phagosomes into phagolysosomes. Maturation of phagosomes into phagolysosomes was not observed with carboxylated beads or pigment particles. In addition, phagocytosis of E. coli and collagen I-coated beads led to increased lysosomal mass, and the specific up-regulation and activity of cathepsin B (CTSB). Higher levels of membrane-bound and secreted CTSB were also detected. Moreover, in vivo zymography showed the intralysosomal degradation of ECM components associated with active CTSB, as well as an overall increased gelatinolytic activity in phagocytically challenged TM cells. This increased gelatinolytic activity with phagocytosis was partially blocked with an intracellular CTSB inhibitor. Altogether, these results suggest a potential role of phagocytosis in outflow pathway tissue homeostasis through the up-regulation and/or proteolytic activation of extracellular matrix remodeling genes.